Moral Believer or Moral Problem-Solver? Moral Pragmatism Fosters Tolerance Without Impeding Moral Behavior - Li Zhang; Song Tong; Kaiping Peng (Behavioral Sciences)
Many previous studies in moral psychology have described people as moral believers, who treat morality as universal sacred beliefs and show moral outrage and social exclusion toward people with different opinions. At the same time, moral relativism tends to make people more tolerant but also makes them question their own beliefs and leads to more immoral behavior. We propose moral pragmatism as an alternative, which treats morality as a tool for solving specific problems, thus making morality situational instead of universal, practical instead of sacred, and tolerant instead of exclusive. Through four empirical studies, we demonstrate that when moral issues are presented as practical problems rather than abstract beliefs, people consider morality to be less universal, treat dissidents with more tolerance and less outrage, and do not perform more immoral behavior at the same time. These findings highlight moral pragmatism as a flexible and culturally sensitive moral approach, promoting diverse moral perspectives and constructive cross-cultural discourses.